2021
DOI: 10.3390/nu13114011
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Substitution in Decompensated Liver Cirrhosis: Don’t Forget Zinc

Abstract: Decompensated liver cirrhosis has a dismal prognosis, with patients surviving on average for 2–4 years after the first diagnosis of ascites. Albumin is an important tool in the therapy of cirrhotic ascites. By virtue of its oncotic properties, it reduces the risk of cardiovascular dysfunction after paracentesis. Treatment with albumin also counteracts the development of hepatorenal syndrome and spontaneous bacterial peritonitis. More recently, the positive impact of long-term albumin supplementation in liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 126 publications
(190 reference statements)
0
15
0
2
Order By: Relevance
“…To date, some notable progress has been made in this area [ 66 ]. As an essential micronutrient in foods and mineral supplements, zinc has been examined in many clinical trials for the possible prevention of gynecological cancers [ 64 ], like breast [ 26 ] and ovarian cancers [ 65 ], gastrointestinal and hepatic cancers [ 67 , 68 , 69 , 70 ], and lung [ 71 ] and oral cancers [ 72 ], in addition to cardiovascular disease (CVD) [ 73 , 74 ]. However, if breast cancers sequester and use more zinc than normal cells, therapeutic use of an excessive amount of zinc needs to be examined in animal models before any attempt at clinical trials for cancer treatment.…”
Section: Zinc and The Cmpn/cmp Signaling Networkmentioning
confidence: 99%
“…To date, some notable progress has been made in this area [ 66 ]. As an essential micronutrient in foods and mineral supplements, zinc has been examined in many clinical trials for the possible prevention of gynecological cancers [ 64 ], like breast [ 26 ] and ovarian cancers [ 65 ], gastrointestinal and hepatic cancers [ 67 , 68 , 69 , 70 ], and lung [ 71 ] and oral cancers [ 72 ], in addition to cardiovascular disease (CVD) [ 73 , 74 ]. However, if breast cancers sequester and use more zinc than normal cells, therapeutic use of an excessive amount of zinc needs to be examined in animal models before any attempt at clinical trials for cancer treatment.…”
Section: Zinc and The Cmpn/cmp Signaling Networkmentioning
confidence: 99%
“…Hepatocyte-protecting drugs such as glutathione, ganning tablets, silymarin, inosine and vitamins C, E and B groups can improve liver cell metabolism, prevent fatty degeneration and protect liver cells (22). For hypoalbuminemia and ascites, although treatments such as ALB infusion and diuretics have a certain curative effect, they cannot solve the fundamental problem of DLC, thus DLC gradually leads to liver failure (23,24). The present study revealed that the routine drug treatment for DLC, which was administered for 1 year, led to no significant changes in liver function and blood indexes.…”
Section: Discussionmentioning
confidence: 55%
“…As shown in Figure 4, the step following sodium restriction should be improvement of hypoalbuminemia, and treatment for this should be initiated before addition of a diuretic to the treatment regimen. Patients with cirrhosis and ascites usually display hypoalbuminemia because of their liver's reduced capacity for protein synthesis 21 . As diuretics have no therapeutic effect on hypoalbuminemia, and, importantly, conventional diuretics cannot exert their effects until they bind to albumin, it is crucial to improve hypoalbuminemia when administering diuretics 11,12 .…”
Section: Seven Steps In the Treatment Of Cirrhotic Ascitesmentioning
confidence: 99%